2019
DOI: 10.1038/s41598-019-41792-z
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Large Magnetic-Field-Effects on the Impedance Response of TiO2 Quantum Dots

Abstract: Here, we report large magnetoresistance and magnetocapacitance response of undoped TiO 2 quantum dots weighting the contribution of both grain and grain boundaries by means of impedance spectroscopy. We also performed a complete characterization of the TiO 2 quantum dots (~5 nm) prepared by sol-gel via water vapor diffusion method, using X-ray diffraction, small angle X-ray scattering, transmission electron microscopy and Raman spectroscopy. In addition, we showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The preparation of P3HT:TiO 2 nanocomposites was based on the sol-gel synthesis via water vapor flow diffusion, as it was previously reported for other polymers [ 27 , 28 , 29 ]. In total, 0.3 g of regioregular poly(3-hexylthiophene-2,5-diyl) (P3HT) polymer, purchased from Sigma-Aldrich with a M w of 50,000–100,000 and a regioregularity above 90%, were suspended in 50 mL of tetrahydrofuran (THF) and kept stirred at T = 70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of P3HT:TiO 2 nanocomposites was based on the sol-gel synthesis via water vapor flow diffusion, as it was previously reported for other polymers [ 27 , 28 , 29 ]. In total, 0.3 g of regioregular poly(3-hexylthiophene-2,5-diyl) (P3HT) polymer, purchased from Sigma-Aldrich with a M w of 50,000–100,000 and a regioregularity above 90%, were suspended in 50 mL of tetrahydrofuran (THF) and kept stirred at T = 70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, DFT studies on the electronic interactions of tetrafluoro-tetracyanoquinodimethane (F4-TCNQ)/ZnO surfaces ( Xu et al, 2013 ), hexafluoro-tetracyano-naphthoquinodimethane (F6-TCNNQ)/ZnO surfaces ( Schöttner et al, 2020 ), oligothiophenes and ZnO (and In-doped SnO 2 ) surfaces ( Timpel et al, 2020 ) has shed some light on the work function and other relevant electronic properties of these h OI interfaces. Other DFT studies on the electronic interactions between larger and more complex systems such as polyaniline oligomer/graphene oxide quantum dots (GQD) including edge functionalization ( Mombrú et al, 2017c ) and vinyl carbazole monomer/TiO 2 surfaces including oxygen and titanium vacancy defects ( Mombrú et al, 2019a ; Mombrú et al, 2019b ) has shown interesting features on the electronic properties evidencing the relevance of using more realistic models as depicted in Figure 2B . For instance, the difference between the LUMO level of vinyl carbazole and the conduction band of TiO 2 surface with oxygen vacancies decreases thus favoring the energy barrier associated with the charge injection at this h OI interface ( Mombrú et al, 2019b ).…”
Section: Mixed Ionic-electronic Transport Of H Oi ...mentioning
confidence: 99%